2015
DOI: 10.1021/acsmacrolett.5b00164
|View full text |Cite
|
Sign up to set email alerts
|

Linear, Single-Strand Heteroaromatic Polymers from Superacid-Catalyzed Step-Growth Polymerization of Ketones with Bisphenols

Abstract: Novel, linear, high-molecular-weight single-strand heteroaromatic polymers and copolymers containing 9H-xanthene moieties in the backbone were synthesized by metal-free superacid-catalyzed stoichiometric and nonstoichiometric step-growth polymerizations of carbonyl compounds bearing electron-withdrawing substituents with bisphenols. The electrophilic aromatic substitution reactions of ketones with phenol fragments occur exclusively in ortho-positions to the hydroxy phenol group and followed by highly efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…Although it has been proposed that superacid catalyzed polyhydroxyalkylations deviate significantly from the classical behavior of A 2 + B 2 step‐growth polymerizations, there are no kinetic modeling studies, focused on molecular weight development, reported for this system, which can explain such deviations. It is our objective in this contribution to propose a kinetic model for superacid catalyzed polyhydroxyalkylations focused on molecular weight development.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although it has been proposed that superacid catalyzed polyhydroxyalkylations deviate significantly from the classical behavior of A 2 + B 2 step‐growth polymerizations, there are no kinetic modeling studies, focused on molecular weight development, reported for this system, which can explain such deviations. It is our objective in this contribution to propose a kinetic model for superacid catalyzed polyhydroxyalkylations focused on molecular weight development.…”
Section: Introductionmentioning
confidence: 92%
“…Since the reaction proceeds between A and B only (A does not react with itself and the same occurs with B), this will result in a reduction of molecular weight. However, in superacid catalyzed polyhydroxyalkylations the experimental evidence shows that increasing the excess of one of the functional groups (isatin), which is equivalent to decreasing r in Equation , will result in an increase in molecular weight . In order to account for this observation, in this work we assumed that the four reactions of the polymerization scheme shown in Equations – react at different rates, namely, instead of having a single kinetic rate constants, k , we have four: k ab , k am , k bm , and k mm .…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Super acid-catalyzed (Friedel-Crafts aromatic electrophilic substitution reaction) reaction has gaining remarkable interest in recent past [19][20][21][22][23][24] because of their myriad advantages associated with eco-friendliness. Super acidcatalyzed reactions have the following advantages: the reaction proceeds at room temperature, structural selection and easy availability of monomers, high yields and selectivity, short duration of reaction, more versatility in polymer architectures, easy purification, possessing good physical, chemical, and thermal properties of the synthesized polymers, and high molecular weights, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several reactions have been performed using super acids [mostly trifluoromethanesulfonic acid (TFSA)] and open up a new avenue in chemistry. The dramatic use of super acid catalyst in hydroxyalkylation reactions [29], polyhydroxyalkylation [20], and synthesis of hyper-branched polymers [19,38] was progressively reported.…”
Section: Introductionmentioning
confidence: 99%